Virtual Reality to Relieve Pain in Burn Patients Undergoing Imaging and Treatment. Issue 4 (August 2020) - Bermo, Mohammed S.; Patterson, David; Sharar, Sam R.; Hoffman, Hunter; Lewis, David H.
Abstract : Abstract: Pain from burn injuries is among the most excruciating encountered in clinical practice. Pharmacological methods often fail to achieve acceptable level of analgesia in these patients, especially during burn wound dressing and debridement. Virtual reality (VR) distraction is a promising analgesic technique that progressed significantly in the last decade with development of commercially available, low-cost, high-resolution, wide field-of-view, standalone VR devices that can be used in many clinical scenarios. VR has demonstrated clinical benefit as an adjunctive analgesic during burn wound dressing and other painful medical procedures. The technique has proven useful also in preparing patients for magnetic resonance imaging scans, particularly in claustrophobic patients. Modulation of pain-related brain activity at cortical and subcortical levels by VR, and its correlation with subjective improvement in various laboratory and clinical pain experiences has been demonstrated using multiple functional brain imaging studies including functional magnetic resonance imaging and brain perfusion single photon emission computed tomography.